Research Progress and Prospects of Urban-Rural Integration Based on Scientific Knowledge Map - Gong Weixia; Ma Shujiao (Redai dili)
Promoting urban-rural integration is a critical pathway for coordinating China's new urbanization and comprehensive rural revitalization and is essential for achieving socialist modernization and common prosperity. Currently, urban-rural integration is at a key transitional stage, making it vital to systematically review and synthesize existing research. This study employed CiteSpace software to visually analyze 2,164 papers on urban-rural integration between 2002 and 2023 from the CNKI database. The analysis comprehensively presents research progress in terms of publication volume, authors, institutions, research areas, hot topics, evolution trajectories, and frontier trends, while also providing insights into future development trends. This study reveals that, over the past two decades, domestic research on urban-rural integration has shown significant and sustained growth driven by policy initiatives. However, the field has not yet formed a stable core group of authors and collaboration among researchers remains relatively limited and is often confined to intra-institutional partnerships. The key research themes focused on the evolution and development of urban-rural relations, the connotations and significance of urban-rural integration, the connection between urban-rural integration and rural revitalization, influencing factors, and development paths. The research evolution can be divided into four stages: early exploration, gradual development, consolidation and deepening, and expansion and innovation. Over the past three years, research frontiers have focused on poverty alleviation, metropolitan area construction, and the exploration of development paths. Current research shortcomings include the following. (1) Insufficient analysis of regional types and scale differences: the research lacks a comprehensive multiscale framework and does not adequately focus on special geographical spaces. Studies on the mechanisms of urban-rural interconnection and coordinated development between regions are also weak; (2) An analysis of multiple factors influencing urban-rural integration is lacking: current research has not sufficiently explored obstructive factors, the interactions between these factors, their combined effects, or regional heterogeneity; (3) The multidimensional evaluation system and data application are inadequate: traditional data sources lack timeliness and comprehensiveness and evaluation indicators have overlapping issues and insufficient representativeness; and (4) Integration of interdisciplinary perspectives is insufficient: much of the research has been limited to single-discipline approaches and lacks comprehensive interdisciplinary analysis. This study proposes the following recommendations: (1) Strengthen multi-disciplinary, multi-dimensional, and multi-scale research: this includes enhancing interdisciplinary collaboration, innovating theories and methods, and building multilevel research systems to explore the spatial and temporal evolution of urban-rural integration across different scales; (2) Deepen research on the coupling and coordination between new types of urbanization and comprehensive rural revitalization: this involves exploring coordination mechanisms, refining the flow of key elements, discovering new models of urban-rural industrial integration, and promoting cultural exchange and integration; (3) Strengthen regional coordination research; expanding research fields, summarizing integration models from different regions, enhancing regional coordination and joint development, and building multiscale regional coordination mechanisms are essential; and (4) Advanced technological innovation and data-driven research: this includes using cutting-edge technologies to reveal trends in urban-rural integration, scientifically predicting urbanization processes, and driving industrial synergy and transformation.